2004
DOI: 10.1017/s1743921304006933
|View full text |Cite
|
Sign up to set email alerts
|

Science Goals and Development of the Advanced Technology Solar Telescope

Abstract: Abstract. The Advanced Technology Solar Telescope (ATST) will perform high-resolution studies of the Sun's magnetic fields needed to understand their role in the fundamental processes responsible for solar variability. The generation of magnetic fields through dynamo processes, the amplification of fields through the interaction with plasma flows, and the destruction of fields remain poorly understood. There is incomplete insight as to what physical mechanisms are responsible for heating the corona, what cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…For a more sophisticated investigation, a much higher spatial resolution is required as will be provided by a new generation of telescopes like GREGOR (see Volkmer et al 2005) or the ATST (see Keil et al 2004). Several spectral lines sensitive to different heights should be observed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…For a more sophisticated investigation, a much higher spatial resolution is required as will be provided by a new generation of telescopes like GREGOR (see Volkmer et al 2005) or the ATST (see Keil et al 2004). Several spectral lines sensitive to different heights should be observed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…They obtained full Stokes profiles of limb coronal fields and found that field strength is about 4 G at 100 in height above the photosphere. One of the main purposes of the Advanced Technology Solar Telescope (ATST) is to observe coronal magnetic fields (see Keil et al 2004 and their Web site 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…目前国际上 1 m以上的太阳望远镜共有4架, 包括美国大熊湖天 文台1.6 m太阳望远镜(GST) [8] 、位于加那利群岛的 德国1.5 m太阳望远镜(GREGOR)、 瑞典1 m太阳望 远镜(SST) [9] 和我国的1 m真空太阳望远镜(NVST). 正在建设中的大望远镜有美国国立天文台4 m太 阳望远镜(DKIST) [10] . 规划中的大望远镜包括: 欧 洲的4 m太阳望远镜(EST) 1) 和印度的2 m太阳望远 镜(NLST) [11] .…”
Section: 国内外同类观测设备的研究现状和发展 趋势unclassified